Bayesian spatio-temporal modeling of real estate launch prices - Rocio, Vitor Dias; Laurini, Márcio Poletti (Journal of Spatial Econometrics, 2023)
In this study, we utilize Bayesian methods to construct a comprehensive spatio-temporal model for real estate launch prices in the city of São Paulo. Our approach involves the decomposition of the price series into trend and cycle components, as well as the inclusion of spatially continuous and time-varying random effects. Additionally, we incorporate a set of explanatory variables to account for hedonic aspects. Within the hedonic components, we not only consider intrinsic property characteristics but also take into consideration neighborhood features and the economic environment. With the application of this model, we have successfully estimated equilibrium prices for various locations, offering a more transparent interpretation of property price dynamics spanning from January 2000 to December 2013 within São Paulo city.